The Core and Periphery of The Concept “Youth” In the Uzbek Language - Abduazizova Munisa Muzaffar Qizi (American Journal Of Social Sciences And Humanity Research, 2025)
In the lexicon of the Uzbek language, the word “youth” embodies multifaceted semantic features. Although the concept of “youth” initially existed as a biological category, its meaning is somewhat complex, broad and multi-layered. This article analyzes such fundamental and peripheral layers of meaning in the concept of “youth” and discusses their cultural identity.